Making Things Perfectly Queer : Interpreting Mass Culture - Doty, Alexander (Book collections on Project MUSE., 1993)
Doty demonstrates how queer readings can be--and are--performed by examining star images like Jack Benny and Pee-wee Herman, women-centered sitcoms like Laverne and Shirley and Designing Women, film directors like George Cukor and Dorothy Arzner, and genres like the musical.